BIOSORPSI ION Cr(III) PADA RUMPUT LAUT Eucheuma Spinosum TERAKTIVASI ASAM SULFAT - Sudiarta, I W. (Jurnal Kimia (Journal of Chemistry); Vol. 3, No. 2 Juli 2009)
Biosorption of chromium(III) ion on sulfuric acid activated algae (Eucheuma spinosum) biosorbent have been studied in this research. The studies included determination of optimum ratio of sulphuric acid to biosorbent algae, biosorbent acidity, isoterm and biosorption capacity, and interaction mechanisms of Cr(III) on biosorbent. The mechanisms interaction of Cr(III) on biosorbent can be determinted from the sequential desorption of Cr(III) using H2O, 1M HCl and 0.05M Na2EDTA. The result showed that the optimum ratio of sulphuric acid to biosorbent was 1.5 mmol/g. It was also found that the total acidity of acid-activated and untreated algae biosorbent were 8.56±0.21 and 2.59± 0.28 mmol/g respectively. The biosorption capacity of activated biosorbent toward Cr(III) was 72.33 mg/g while the capacity of untreated biosorbent was 57.32 mg/g. The interaction mechanisms of Cr(III) with biosorbent were found to be mainly through the ionic interaction, while the interaction through hydrogen bonding, van der Walls, and complexation were found to be relative us low.
Keywords: Biosorption, Cr(III), Acid-activated, Eucheuma spinosum